UPAYA GURU BK MENANAMKAN KONSEP DIRI POSITIF TERHADAP SISWA TAWURAN - Sulfikar k; Casmini Casmini (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The background of this research is based on the rise of brawls in the environment of middle school students increasing every year. Even though in educational institutions there have been various efforts implemented so that students have the behavior as expected in every educational institution. Therefore, this study aims to look at what factors are causing brawls among junior high school students and find out what efforts are being made by BK teachers who are in school in solving brawl problems. The research method in this research is to use a qualitative approach with descriptive methods. The research instrument uses observation, interviews and documentation. The technique of determining the subject using purposive sampling with data analysis techniques in this study is the qualitative analysis method from Miles and Huberman. The results showed that there were many factors influencing students to fight, one of them was due to trivial matters. In addition, BK teacher's efforts have also been made in dealing with students who have brawled.